2018
DOI: 10.1186/s12887-018-0997-y
|View full text |Cite
|
Sign up to set email alerts
|

Next wave of interventions to reduce under-five mortality in Rwanda: a cross-sectional analysis of demographic and health survey data

Abstract: BackgroundSustained investments in Rwanda’s health system have led to historic reductions in under five (U5) mortality. Although Rwanda achieved an estimated 68% decrease in the national under U5 mortality rate between 2002 and 2012, according to the national census, 5.8% of children still do not reach their fifth birthday, requiring the next wave of child mortality prevention strategies.MethodsThis is a cross-sectional study of 9002 births to 6328 women age 15–49 in the 2010 Rwanda Demographic and Health Surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 17 publications
3
11
0
Order By: Relevance
“…Under-five childhood mortality is significantly higher among children belonging to mothers who do not use and do not intend to use contraceptive compared to their counterparts from mothers who use modern contraceptive method. Also, the likelihood of under-five mortality increases with total children ever born and number of births in last 5 years and these findings are consistent with previous studies [15, 18, 25]. All these variables are related to family planning.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Under-five childhood mortality is significantly higher among children belonging to mothers who do not use and do not intend to use contraceptive compared to their counterparts from mothers who use modern contraceptive method. Also, the likelihood of under-five mortality increases with total children ever born and number of births in last 5 years and these findings are consistent with previous studies [15, 18, 25]. All these variables are related to family planning.…”
Section: Discussionsupporting
confidence: 92%
“…The likelihood of child survival decreased among children who are products of multiple births compared to their counterparts who were products of singletons. Low birthweight or competition for nutritional intake which occurs more among children who are products of multiple births could be a plausible explanation [11, 22, 25]. This study also showed that being a female child decreased the likelihood of under-five mortality.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Monden and Smits (2017) show that mortality among under five children who were products of multiple births is 3 times higher than the mortality among singletons in sub-Saharan Africa [ 22 ]. This could partly be attributable to competition for nutrients and health complications that usually occur more among children who are products of multiple births [ 3 , 17 , 19 , 23 ]. The unexpected finding that the number of children under-five in household is associated with lower risk of U5M warrants further investigation as reported in a previous study [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is also expected to result in optimal childcare and feeding practices with its resultant improved health outcomes for the child [3,[17][18][19]. U5M is significantly higher among children born multiple compared to those born singleton which could be due to competition for nutrients and health complications that usually occur more among children who are products of multiple births [3,17,19,20]. The unexpected finding that the number of children under-five in household is protective of U5M warrants further investigation as reported in a previous study [3].…”
Section: Discussionmentioning
confidence: 78%